2017
DOI: 10.1210/js.2017-00044
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Incident Type 1 and Type 2 Diabetes in Children and Young Adults: A Retrospective Cohort Study

Abstract: Context:Little is known about the association between obesity and temporal trends in the incidence of diabetes in children and young adults.Objective:We examined the recent incidence of types 1 and 2 diabetes in relation to a high body mass index (BMI) in UK children and young adults.Design:Cohort and nested case-control.Setting:A total of 375 general practices that contribute to the UK Clinical Practice Research Datalink (CPRD).Participants:A total of 369,362 participants aged 2 to 15 years at BMI measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 39 publications
3
120
1
1
Order By: Relevance
“…In the United States, close to one in three adults over the age of 65 years have T2DM. Ninety percent of people with T2DM have overweight or obesity, and the presence of obesity accelerates the development of T2DM . Children with T2DM were rarely reported in the 1980s .…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, close to one in three adults over the age of 65 years have T2DM. Ninety percent of people with T2DM have overweight or obesity, and the presence of obesity accelerates the development of T2DM . Children with T2DM were rarely reported in the 1980s .…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 99%
“…As the incidence of obesity in children climbed over the past 30 years, so too did the prevalence of T2DM . It is estimated that, compared to those with a normal BMI, the incidence of T2DM is four times higher in children with obesity . Moreover, BMI changes the lifetime risk of T2DM.…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 99%
“…Obese children are more likely to become obese adults [17], further increasing their risks for higher rates of T2DM, heart diseases, and some cancers later in life. A recent large cohort study found that a child with obesity faces a 4-fold greater risk of being diagnosed with T2DM by age 25 than a counterpart who is normal weight [18•]. Another well-powered meta-analysis also found that individuals in the highest quantile of SSB intake (most often 1 −2 servings/day) had a 26% greater risk of developing T2DM than those in the lowest quantile (none or < 1 serving/month).…”
Section: Introductionmentioning
confidence: 99%
“…Table S2) [1,15]. Although obesity is one of the metabolic syndrome parameters, its link with youth-onset T2D has been investigated separately (e.g., [16,17]). Children and adolescents from the United Kingdom who were within the obesity category had a 4.3 greater risk of T2D compared with their normal-weight peers [16].…”
Section: Resultsmentioning
confidence: 99%
“…Although obesity is one of the metabolic syndrome parameters, its link with youth-onset T2D has been investigated separately (e.g., [16,17]). Children and adolescents from the United Kingdom who were within the obesity category had a 4.3 greater risk of T2D compared with their normal-weight peers [16]. A similar increased risk for children with obesity was also found in a prospective study of American Indians, where the relative risk of developing T2D ranged from 2.3 to 7.4, depending on gender, age, and degree of overweight [17].…”
Section: Resultsmentioning
confidence: 99%